An international survey of health literacy education within schools of pharmacy - Swinburne, G.; Duncan, G.; McNamara, K.; Stewart, K.; Emmerton, Lynne; Hussainy, S. (International Pharmaceutical Federation, 2014)
Background: Health literacy (HL) influences patients’ health status, use of the healthcare system and medication-related behaviours. However, the concept is relatively new to pharmacy and its incorporation in academic curricula has not been examined. Aims: To explore HL training in pharmacy schools internationally, and academics’ opinions in regards to how it should be taught and assessed. Methods: An anonymous, online survey was administered to academics who teach within pharmacy degree courses from countries where English is the main language. Results: Responses were received from 21 pharmacy schools in seven countries; 20 stated that HL was taught within their pharmacy degree, in four as a stand-alone topic. Small-group tutorials were thought to be the most beneficial form of teaching health literacy, best assessed using oral and objective structured clinical examinations. Conclusion: The majority of pharmacy schools taught health literacy and had similar opinions regarding best practice teaching and assessment.